Toxicity differences of polystyrene nanoplastics (PS-NPs) and polylactic acid nanoplastics (PLA-NPs) on the Paramecium bursaria - Chlorella symbiotic system - Zehua Hu; Han Gong; Yuanyin Huang; Yezi Wang; Chao Li; Muting Yan (Environmental Pollution, 2026)

Making waves: Impaired osmotic reserve by chemical exposure amplifies vulnerability of estuarine organisms to climate-driven salinity shifts - Ruting Yang; Dali Wang; Yao-Ping Wang; Muting Yan; Huizhen Li; Jing You (Water Research, 2026)

Mechanistic insights into toxic effects of silver nanoparticles on fish - Cuiming Huang; Muting Yan; Xiaoling Wei; Jinlian Huang; Lijie Xu; Lu Gan; Wei Chu; Han Gong (Gondwana Research, 2026)

Antagonistic effect of polystyrene nanoplastics and sliver nanoparticles on Chlorella pyrenoidosa - Feng Li; Jinlian Huang; Xiaoling Wei; Zeshi Gong; Lijie Xu; Lu Gan; Wei Chu; Muting Yan; Han Gong (Journal of Environmental Sciences, 2026)

Role of microplastics in mediating the transmission of antibiotic resistance gene tet from antibiotic-resistant bacteria to Litopenaeus vannamei - Xilin Fang; Han Gong; Riying Zhong; Ziyu Liu; Yezi Wang; Muting Yan (Journal of Environmental Management, 2026)

Comparative study on degradation of PVC microplastics under four processes: mechanism, pathway and toxicological assessment - Ruixue Li; Muting Yan; Cuiming Huang; Xiaoling Wei; Lijie Xu; Lu Gan; Luyi Pan; Wei Chu; Xudai Wu; Zhenfei Han; Han Gong (Gondwana Research, 2025)

Polyvinyl chloride microplastics facilitated the transmission of Vibrio parahaemolyticus from surrounding water to Litopenaeus vannamei - Weixin Li; Ziying Zhu; Xilin Fang; Xiaocui Wang; Wei Chu; Han Gong; Muting Yan (Food Microbiology, 2025)

W2O6/CoFe2O4: An efficient catalyst to activate peroxymonosulfate for the elimination of antibiotic-resistant bacteria and genes in aquaculture effluent - Yanqiong Zhang; Muting Yan; Gaoling Wei; Fengru Lu; Feng Li; Peng Liu; Yanping Zhu; Han Gong (Journal of Environmental Chemical Engineering, 2025)

Microparticles introduced by the processing of traditional Chinese medicine Hirudo nipponica Whitman might pose threat to patients - Muting Yan; Xilin Fang; Riying Zhong; Houxiang Zhang; Ziying Zhu; Han Gong; Muxian Yan (Food and Chemical Toxicology, 2025)

Microplastics Enhance the Toxic Effects of Tetracycline on the Early Development of Zebrafish in a Dose-Dependent Manner - Yanqing Wu; Ziying Zhu; Riying Zhong; Xilin Fang; Xiaocui Wang; Yuanyin Huang; Han Gong; Muting Yan (Fishes, 2025)
Microplastic pollution in the environment has greatly increased due to the widespread use of plastics. Antibiotics and microplastic are common contaminants, especially in aquaculture. Microplastics could act as antibiotic vectors that raise the potential of their ecotoxicological effects. In this work, we conducted several analyses of biomarker responses to examine the developmental toxicity and toxicological endpoints that polyethylene microplastics (PE-MPs) and tetracycline antibiotics (TC) induced in zebrafish (Danio rerio) embryos/larvae. The results suggested that TC-PE-MPs induced significant physiological perturbations, including attenuated spontaneous cardiac contractions, cardiotoxicity, a dose-dependent elevation in mortality, and a marked reduction in body length, accompanied by morphological alterations. The mechanistic analysis revealed that ROS accumulation triggered enzymatic activity changes, which further induced aberrant vascular development, robust inflammatory responses, and dysregulated gene expression. These findings demonstrate that PE coexistence potentiates TC’s toxicological effects, with combined exposure inducing developmental toxicity during critical organogenesis stages in zebrafish. Overall, the current research demonstrated the detrimental effects of TC-PE-MPs on early fish development, suggesting potential environmental risks.

Bacillus subtilis, a promising bacterial candidate for trapping nanoplastics during water treatment - Ziying Zhu; Yanqing Wu; Xilin Fang; Riying Zhong; Han Gong; Muting Yan (Journal of Hazardous Materials, 2025)

Bacterial degradation of polyethylene and polypropylene microplastics in a mangrove ecosystem - Riying Zhong; Minqian Li; Ziying Zhu; Xilin Fang; Xiaocui Wang; Han Gong; Muting Yan (Chemosphere, 2024)

Pseudomonas Stutzeri may alter the environmental fate of polystyrene nanoplastics by trapping them with increasing extracellular polymers - Ziying Zhu; Han Gong; Riying Zhong; Xiaocui Wang; Ziyu Liu; Yuanyin Huang; Muting Yan (Science of The Total Environment, 2024)

Microplastics in tea from planting to the final tea product: Traceability, characteristics and dietary exposure risk analysis - Daiman Xing; Tangmilan Zhao; Xindong Tan; Jing Liu; Shihan Wu; Jingyu Xu; Muting Yan; Binmei Sun; Shaoqun Liu; Peng Zheng (Food Chemistry, 2024)

Mangrove plants are promising bioindicator of coastal atmospheric microplastics pollution - Yuanyin Huang; Ziying Zhu; Tianmu Li; Minqian Li; Zeming Cai; Xiaocui Wang; Han Gong; Muting Yan (Journal of Hazardous Materials, 2024)

Combined effects of microplastics and antibiotic-resistant bacteria on Daphnia magna growth and expression of functional genes - Xiaofeng Chen; Xiaocui Wang; Yuanyin Huang; Ziying Zhu; Tianmu Li; Zeming Cai; Minqian Li; Han Gong; Muting Yan (Science of The Total Environment, 2023)

Microplastic pollution in water environment of typical nature reserves and scenery districts in southern China - Han Gong; Ruixue Li; Feng Li; Lijie Xu; Lu Gan; Jingxian Li; Haisheng Huang; Muting Yan; Jun Wang (Science of The Total Environment, 2023)

Occurrence and removal of antibiotics from aquaculture wastewater by solar-driven Fe(VI)/oxone process - Han Gong; Ruixue Li; Yanqiong Zhang; Lijie Xu; Lu Gan; Luyi Pan; Minxing Liang; Xue Yang; Wei Chu; Yuan Gao; Muting Yan (Chemosphere, 2023)

Adverse effects of silver nanoparticles on aquatic plants and zooplankton: A review - Feng Li; Ruixue Li; Fengru Lu; Lijie Xu; Lu Gan; Wei Chu; Muting Yan; Han Gong (Chemosphere, 2023)

Microplastics in marine-derived traditional Chinese medicine, potential threat to patients - Ziying Zhu; Han Gong; Xiaocui Wang; Xukun Wang; Wenqian Guo; Muxian Yan; Muting Yan (Science of The Total Environment, 2023)

Removal of antibiotic-resistant bacteria and genes by Solar-activated Ferrate/ Peroxymonosulfate: Efficiency in aquaculture wastewater and mechanism - Ruixue Li; Xudai Wu; Zhenfei Han; Lijie Xu; Lu Gan; Yanqiong Zhang; Fengru Lu; Hua Lin; Xue Yang; Muting Yan; Wei Chu; Han Gong (Chemical Engineering Journal, 2023)

Toxicity of nanoplastics to aquatic organisms: Genotoxicity, cytotoxicity, individual level and beyond individual level - Han Gong; Ruixue Li; Feng Li; Xiaowen Guo; Lijie Xu; Lu Gan; Muting Yan; Jun Wang (Journal of Hazardous Materials, 2023)

Microplastic pollution and enrichment of distinct microbiota in sediment of mangrove in Zhujiang River estuary, China - Muting Yan; Xiaofeng Chen; Wei Chu; Weixin Li; Minqian Li; Zeming Cai; Han Gong (Journal of Oceanology and Limnology, 2023)

A mitochondrial outer membrane-localized protein encoded by White spot syndrome virus - Muting Yan; Lihong Liu; Qianhui Liang; Jianhui He; Shaoping Weng; Jianguo He; Xiaopeng Xu (Virus Genes, 2016)